2020
DOI: 10.34172/hpp.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Global policy responses to the COVID-19 pandemic: proportionate adaptation and policy experimentation: a study of country policy response variation to the COVID-19 pandemic

Abstract: Background: Concern for the development of actions against COVID-19 has continued to grow since February 2020. Government responses remain a crucial part of preventing virus transmission through policy formulation and strengthening national capacity. Methods: This study has used quantitative analysis, using secondary data from 177 countries. The variables consist of Global Health Security (GHS) category and COVID-19 pandemic. An analysis of the appropriateness of the government’s policy response in dealing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
(40 reference statements)
0
37
0
1
Order By: Relevance
“…Several studies have shown that morbidity of influenza could be decreased after conduction of NPIs [38,39] . And a study analyzed whether various governmental policies for addressing the COVID-19 pandemic in 177 countries were appropriate, finding different reaction degrees of these countries and suggesting that governments should promote their response facing COVID-19 [40] . Therefore, we speculated that country's policy was one of the influence factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that morbidity of influenza could be decreased after conduction of NPIs [38,39] . And a study analyzed whether various governmental policies for addressing the COVID-19 pandemic in 177 countries were appropriate, finding different reaction degrees of these countries and suggesting that governments should promote their response facing COVID-19 [40] . Therefore, we speculated that country's policy was one of the influence factors.…”
Section: Discussionmentioning
confidence: 99%
“…This research uses this method, qualitative research with literature review [31,32]. The literature review was carried out as a comparison of previous findings that had not been found by previous researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Indonesian government just ruled out the instructions of physical distancing by the end of March [16]. A previous study also reported that in terms of pandemic policy response, Indonesia was one of the countries with the medium case yet having a proportional response towards the pandemic [32]. Therefore, this might lead to a reduced public trust that subsequently decreases the response and self-efficacy of the people in the western region, where the regulations took place earlier.…”
Section: Risk Perception: Protection Motivation Theory (Pmt) Constructsmentioning
confidence: 99%